2023
DOI: 10.35848/1882-0786/acace8
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient operation and uniform characteristics of curved mirror vertical-cavity surface-emitting lasers

Abstract: This study obtained highly uniform and efficient GaN-based vertical-cavity surface-emitting lasers (VCSELs) with curved mirror from a single wafer. The average threshold current (Ith) and the optical output power (Pmax) of 14 nominally identical chips measured up to 7 mA were 0.64 mA and 4.5 mW, respectively. The standard deviations of Ith and Pmax were 0.043 mA and 0.23 mW, respectively. Additionally, the best chip shows maximum values of wall plug efficiency and output power of 13.4% and 7.6 mW, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…This frequently results in a fabrication error, which can deteriorate the lasing yield. Using a long-cavity structure, lasing with 100% yield and good uniformity of I-V/L have been reported, which support that this structure is stable against fabrication disturbances [13].…”
Section: Vcsel With Curved Mirror and Long Cavitysupporting
confidence: 56%
See 4 more Smart Citations
“…This frequently results in a fabrication error, which can deteriorate the lasing yield. Using a long-cavity structure, lasing with 100% yield and good uniformity of I-V/L have been reported, which support that this structure is stable against fabrication disturbances [13].…”
Section: Vcsel With Curved Mirror and Long Cavitysupporting
confidence: 56%
“…The impact of any loss due to the addition of the filtering mirror was approximately evaluated considering the SE relative to that of the reference DBR structure. It has previously been reported that a device with a 7.5-pair DBR (99.3% reflectivity) showed an SE of 0.83 W A −1 with an internal loss on the order of 1% [19]. Assuming a constant injection efficiency and wavelength, SE comparison provides the internal loss, αi, in an FM sample as follows:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations